2010
DOI: 10.1111/j.1349-7006.2010.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐XL and STAT3 mediate malignant actions of γ‐irradiation in lung cancer cells

Abstract: Previous reports suggest that, in addition to its therapeutic effects, ionizing radiation (IR) increases the invasiveness of surviving cancer cells. Here, we demonstrate that this activity of IR in lung cancer cells is mediated by a signaling pathway involving p38 kinase, phosphoinositide 3-kinase, Akt, and matrix metalloproteinase (MMP-2). The invasion-promoting doses of IR also increased and reduced the levels of vimentin and E-cadherin, respectively, both of which are markers for the epithelial-mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 38 publications
5
68
0
1
Order By: Relevance
“…Indeed, these data were consistent with a recent report that IR enhances the invasiveness of and the events related to the epithelial-mesenchymal transition of lung cancer cells by Bcl-xL accumulation through STAT3, suggesting that STAT3 and Bcl-xL may contribute to the malignancy of lung cancer cells. 34 Notably, in vivo xenotransplanted analysis indicated that cucurbitacin I may be a sensitizer that synergistically enhances both radiosensitivity and chemosensitivity in a xenotransplanted model of human lung CSCs (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these data were consistent with a recent report that IR enhances the invasiveness of and the events related to the epithelial-mesenchymal transition of lung cancer cells by Bcl-xL accumulation through STAT3, suggesting that STAT3 and Bcl-xL may contribute to the malignancy of lung cancer cells. 34 Notably, in vivo xenotransplanted analysis indicated that cucurbitacin I may be a sensitizer that synergistically enhances both radiosensitivity and chemosensitivity in a xenotransplanted model of human lung CSCs (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report demonstrating that the prosurvival Bcl-2 proteins are direct targets of the p53/p21 complex. In addition to cell invasion and death, prosurvival Bcl-2 proteins can regulate various other cellular functions, including autophagy (24)(25)(26)(27), senescence (28)(29)(30), and the epithelial-mesenchymal transition (31)(32)(33)(34). Notably, these cellular functions are also regulated by p53 and p21 (1,2,30,(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Bcl-xL has been found to increase the phosphorylation levels of Akt protein in lung cancer cells (18). In other researches, it was also shown that AKT activation caused EMT characterized by downregulation of numerous epithelial cell-specific proteins (17).…”
Section: Roles Of Bcl-xl In Formation Of Chemo-or Radioresistance Andmentioning
confidence: 99%